The Effect of Promotion and Service on Custumer interest in Ba’i Bitsaman Ajil (BBA) at KSPPS BMT Artha Sejahtera Senori - Eva Fahma Diafil Jilan; Moh. Agus Sifa'; Moch Zaenal Azis Muchtarom (JOURNAL OF SHARIA ECONOMICS, 2022)
The purpose of this study was to determine the effect of promotion and service both partially and simultaneously on the interest of Bai' Bitsaman Ajil (BBA) customers at KSPPS BMT Artha Sejahtera Senori Tuban. In answering these problems, the researchers used a quantitative approach. The population in this study were customers of Bai' Bitsaman Ajil (BBA) KSPPS BMT Artha Sejahtera Senori Tuban. The method of data collection in this study was by distributing questionnaires to 62 BBA product customers. The technique used is purpose sampling, analyzed using Validity Test, Reliability Test, Classical Assumption Test, Calculated F Test, and Partial t Test. The results of this study indicate that the promotion has a partial and significant effect on the interest of BBA customers, as evidenced by the value of t count (2.609) > t table (1.669) with a significance value of 0.011 < 0.05. The service has a partial and significant influence on the interest of BBA customers, as evidenced by the value of t count (3.002) > t table (1.669) with a significance value of 0.004 <0.05. And simultaneously promotion and service have a significant influence on customer interest, as evidenced by the F test, namely F count (21.089) > F table (3.15) with a significance value of 0.00 < 0.05.